Strategies to overcome superbug invasions emerging research and opportunities - Chopra, Dimple Sethi, 1973-; Kaul, Ankur, 1979- (Advances in medical diagnosis, treatment, and care (AMDTC) book series., 2021)
"Recently, there has been an upsurge in microbial infections. Extensive and inappropriate usage of antimicrobial drugs in treating infections has led to the evolution of a resistant strain of microorganisms and irreversible immunosuppression in humans. Medical institutions and hospitals require solutions to combat these contagions in order to avoid future epidemics. Strategies to Overcome Superbug Invasions: Emerging Research and Opportunities highlights current research and potential strategies to prevent the emergence and re-emergence of drug-resistant pathogenic microbial strains. The content within this publication examines biosensing, global initiatives, nanomaterials, and alternative therapies. It is designed for microbiologists, biotechnologists, pharmacists, pharmacologists, virologists, formulation scientists, infectious disease specialists, government officials, policymakers, healthcare practitioners, doctors, nurses, hospital directors, researchers, surgeons, and academicians who are seeking research on innovative solutions for multi-drug-resistant infections."--